2005
DOI: 10.1002/anie.200500484
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenic Allenophanes: An Asymmetric Synthesis of a Bis(alleno)‐bis(butadiynyl)‐meta‐cyclophane

Abstract: We have an ongoing interest in the design and synthesis of novel cyclophanes, many of which contain a twisted conformation that imparts helical chirality [1] to the assembled molecule.[2] This helical chirality is a consequence of the number, type, and combination of unsaturated linkages present in these molecules. The synthesis and design of cyclophanes [3] and cage compounds with high carbon content in novel shapes and supramolecular geometries [4] continues to be a topic of current interest.Allenes are a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Majumdar 49a reported preparation of N -enyne acrydone 97 under PTC conditions and cumulene-type allenamides 96 were proposed as intermediates (Scheme 33). …”
Section: Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Majumdar 49a reported preparation of N -enyne acrydone 97 under PTC conditions and cumulene-type allenamides 96 were proposed as intermediates (Scheme 33). …”
Section: Preparationmentioning
confidence: 99%
“…More recently, Fallis 49b suggested that allenamide 100 [another secondary allenamide] was formed from aniline substituted propargyl phosphonium ether 98 via an initial intramolecular elimination of triphenylphosphine oxide followed by trapping the cumulene intermediate 99 (Scheme 34). …”
Section: Preparationmentioning
confidence: 99%
“…102 affording bicycle [3.2.0] products 296-298 in moderate to good yields (54-66%) without formation of other regioisomers (Scheme 99). 103 Interestingly, reaction of compound (S)-295 containing the chiral L-valine ester moiety, afforded bicycle 298 in greater than 99% ee, which indicates that the reaction proceeded without racemization of the a-amino acid ester.…”
Section: Intramolecular Metal-catalyzed [2+2] Cycloadditionsmentioning
confidence: 99%
“…[5] In addition, the transition-metal-catalyzed intramolecular amino-cyclizations [6] and Tr ost-Hsung N-allenylation [7] methods have also been developed in recent years. Nevertheless,most of the current methods suffer from at least one of the following drawbacks:h arsh reaction conditions (such as use of strong bases,h igh temperature), the requirement of prefunctionalization of substrates,o re mployment noble metals.H ence,ag eneral, mild, and efficient approach to the synthesis of allenamides is highly desired.…”
mentioning
confidence: 99%